Issues around childhood disclosure of HIV status – findings from a qualitative study in West Bengal, India. (27th April 2016) - Das, A.; Detels, R.; Javanbakht, M.; Panda, S.
Abstract: Introduction: Informing the children living with HIV (CLH) about their disease (disclosure) is important from the perspective of disease treatment and overall psychosocial development. There are no published studies that qualitatively explored HIV disclosure‐related issues among CLH in India. Our aim was to provide insights into the perceptions of informal caregivers of CLH regarding childhood disclosure. Methods: Children were defined as those aged <16 years. In‐depth interviews were conducted with 34 primary caregivers of CLH aged 8 to 15 years old who were residing in West Bengal, India. The participants were recruited with the help of a community‐based organization that provides need‐based services to people living with HIV. Results: We obtained caregivers' perspectives on the motivators and barriers of childhood disclosure. Health benefits such as medication adherence emerged as an important motivator, while distress caused by disclosure and potential for stigma were identified as barriers. Health care providers were the preferred disclosers for most caregivers, followed by the caregivers themselves. Some caregivers wanted their child to learn about his/her HIV status by him/herself. There was no consensus among the caregivers about the ideal age for disclosure. Many preferred to wait until the child attained maturity or was of marriageable age. Discussion: Disclosure of HIV status to children is an emotional issue, both for the caregiver and the child. Like most low‐or middle‐income countries, no standardized, age‐appropriate disclosure guidelines exist in India. Our findings advocate adoption of a multi‐faceted approach, including increased availability of social and familial support, for childhood HIV disclosure.